Literature Review : Antibacterial Activity of Various Mangrove Plant Species Extracts - Balqis, Aurelia Corrinna; Kurniawaty, Evi; Maulana, Muhammad; Ramadhian, Muhammad Ricky (CV. Jasa Sukses Abadi, 2024)
The excessive and uncontrolled use of antibiotics has led to antibiotic resistance in pathogenic bacteria, which poses a serious threat to global health. To address this problem, alternative treatments from natural materials, such as mangrove plants, are starting to attract attention. Mangrove plants contain bioactive compounds that have antibacterial potential against various pathogenic bacteria. This study aims to review the antibacterial activity of various mangrove species in Indonesia. The method used was a literature study that included analysis of recent journals on the antibacterial activity of mangrove plants. The results showed that extracts from various mangrove species, such as Bruguiera gymnorrhiza, Rhizophora mucronata, and Heritiera littoralis, had significant antibacterial activity against Gram-positive and Gram-negative bacteria, such as Escherichia coli, Staphylococcus aureus, and Salmonella enterica. The zones of inhibition produced varied between 5 to 20 mm, with the ethanol extract from Bruguiera gymnorrhiza leaves showing the most potent activity. In addition, the assay results showed that the active compounds in the mangrove extracts had the ability to inhibit bacterial growth at low concentrations, indicating great potential for the development of more efficient and economical antibacterial drugs. This study provides evidence that mangrove plant extracts have potential as antibacterial agents that can be further developed for the treatment of infections caused by pathogenic bacteria, thus providing an effective alternative to overcome the problem of antibiotic resistance.